Antibiotic Prophylaxis in the prevention of surgical site infection - Castro, Ana Paula da Silva (2022)
Objective: Understand the effectiveness of antibiotic prophylaxis in the prevention of infection in the operating room. Methodology: This is an integrative review, using the following databases: PubMed, Latin American and Caribbean Literature on Health Sciences (LiLacs), Scielo and Google Scholar, in September 2022, using the Boolean operator "and". Results: Antibiotic treatment in the prevention of infections in the operating room can be a good alternative, however, it is necessary to apply the correct dosage. In addition, nurses can contribute to the effectiveness of prevention by following equipment cleaning and sterilization protocols, in addition to being aware of the amount of medication applied so that they are effective. Conclusion: antibiotic treatment in the prevention of infections in the surgical center can be an effective means, however, it is necessary to consider the correct dosage and also combine with other methods mentioned in this study.